Hermann von Helmholtz and the foundations of nineteenth-century science - Cahan, David (California studies in the history of science ;, 1993)
Hermann von Helmholtz (1821-1894) was a polymath of dazzling intellectual range and energy. Renowned for his co-discovery of the second law of thermodynamics and his invention of the ophthalmoscope, Helmholtz also made many other contributions to physiology, physical theory, philosophy of science and mathematics, and aesthetic thought.